Curriculum Development in Science Education in Vocational School - Rina Maryanti; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to determine the science education curriculum in vocational high schools. We used the literature review method to obtain data. We analyzed the national curriculum in Indonesia regarding science education in vocational schools. The results showed that almost all vocational programs in vocational schools contain material about science education. The science education curriculum was contained in class X material in the content of vocational specialization (C1, C2, and C3), especially integrated science subjects. That is because science material was the basis for studying further material related to scientific phenomena in an applicative way. This research is expected to make it easier for readers to understand science education in vocational schools.